Friendship happens - Aristizabal, Juan Carlos (Íkala, Revista de Lenguaje y Cultura, 1999)
The author of this essay presents us René Char's poetry as a play on thought which abolishes all notions of time, as a space where the outer world breaks through and disseminates into the verses. In this spacelessness, the Other decenters the unity of the self alloing friendship to occur.